Contrasting social and cognitive accounts on overimitation: the role of causal transparency and prior experiences - Schleihauf, Hanna; Breyel, Sabine; Pauen, Sabina; Höhl, Stefanie (Child development, 2018)
Three experiments (N=100) examine the influence of causal information on overimitation. In Experiment 1, atransparent reward location reveals that the reward is unaffected by nonfunctional actions. When 5-year-oldsobserve an inefficient and subsequently an efficient strategy to retrieve a reward, they show overimitation inboth phases—even though the reward is visible. In Experiment 2, children observefirst the efficient then theinefficient strategy. The latter is always demonstrated communicatively, whereas the efficient strategy is pre-sented communicatively (2a) or noncommunicatively (2b). Regardless of whether the efficient strategy isemphasized through communication or not, most children do not switch from the efficient to the inefficientstrategy. Depending on the situation, children base their behavior on social motivations or causal information.